STAT3 in the systemic inflammation of cancer cachexia - Zimmers, Teresa A.; Fishel, Melissa L.; Bonetto, Andrea (Seminars in cell & developmental biology, 2016)
Weight loss is diagnostic of cachexia, a debilitating syndrome contributing mightily to morbidity and mortality in cancer. Most research has probed mechanisms leading to muscle atrophy and adipose wasting in cachexia; however cachexia is a truly systemic phenomenon. Presence of the tumor elicits an inflammatory response and profound metabolic derangements involving not only muscle and fat, but also the hypothalamus, liver, heart, blood, spleen and likely other organs. This global response is orchestrated in part through circulating cytokines that rise in conditions of cachexia. Exogenous Interleukin-6 (IL6) and related cytokines can induce most cachexia symptomatology, including muscle and fat wasting, the acute phase response and anemia, while IL-6 inhibition reduces muscle loss in cancer. Although mechanistic studies are ongoing, certain of these cachexia phenotypes have been causally linked to the cytokine-activated transcription factor, STAT3, including skeletal muscle wasting, cardiac dysfunction and hypothalamic inflammation. Correlative studies implicate STAT3 in fat wasting and the acute phase response in cancer cachexia. Parallel data in non-cancer models and disease states suggest both pathological and protective functions for STAT3 in other organs during cachexia. STAT3 also contributes to cancer cachexia through enhancing tumorigenesis, metastasis and immune suppression, particularly in tumors associated with high prevalence of cachexia. This review examines the evidence linking STAT3 to multi-organ manifestations of cachexia and the potential and perils for targeting STAT3 to reduce cachexia and prolong survival in cancer patients.